DRUG ABUSERS' PERCEPTIONS OF FAMILY ENVIRONMENT - Pumar, Begoña; Ayerbe, Ana; Espina Eizaguirre, Alberto; García, Enrique; Santos, Asunción (Anales de Psicología / Annals of Psychology)
The social environment of a subject has an important influence in overy areas of his social and personal development. With the aim of study the drug abuser' family relationships we have specially observed the concept of family environmment of Moos and we have reviewed the studies about this subject observed specially those in wich it is used the FES (Moos y Moos, 1981). This study aims in the perception of the family environment of 96 families (60 families with a drug abuser and 36 controls without patology). Although the comparison of the profils of the FES in the families of the group of drug abusers doesn't present important devitations related with the normative sample for spanish population, the diferences are marked by a lower level of CO, EX, IC, and SR and higher level of CN in the drug abusers' families related to the controls. Likewise, we have found that the scales of CN together with the Mean Family Environment have the higher significance in order to distinguish the groups, in view of the discriminant analysis done.